Tony Garnett. - Lacey, Stephen (Television series (Manchester University Press), 2007)
Tony Garnett is the first book-length study of one of the most respected and prolific producers working in British television. From ground-breaking dramas from the 1960s such as Up the Junction and Cathy Come Home to the 'must see' series in the 1990s and 2000s such as This Life and The Cops, Garnett has produced some of the most important and influential British television drama. This book charts his career from his early days as an actor to his position as executive producer and head of World Productions, focusing on the ways in which he has helped to define the role of the creative producer.